2017
DOI: 10.15406/joentr.2017.07.00191
|View full text |Cite
|
Sign up to set email alerts
|

Journal of ISSN: 2379-6359 JOENTR Otolaryngology-ENT Research Case Report Volume 7 Issue 1 - 2017 Current Approach to Cerebrospinal Fluid Rhinorrhea Diagnosis and Management

Abstract: Laboratory a) CSF analysis of the fluid. b) Glucose concentration is >30 mg/dl. Neither sensitive nor specific [10,11].c) Beta-2 transfer in is the gold standard (sensitivity of 94% to 100%, and specificity of 98% to 100%), unfortunately not available in many centers, needs 5-7 days [10]. ImagingThis can be classified into primary and secondary:Primary (helpful in the detection of most of the leaks) [12]:i. MRI cisternography: heavily T2-weighted, fast spin-echo, fatsaturated sequences. Better in prone positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Another similarly aimed study found the sensitivity of HRCT and enhanced MR as 88% and 100% respectively. 17,18,19 Individual values for each modality were not calculated in our study, as it aimed to delineate the advantage of combination of two modalities over the use of any single one for diagnosis of CSF rhinorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Another similarly aimed study found the sensitivity of HRCT and enhanced MR as 88% and 100% respectively. 17,18,19 Individual values for each modality were not calculated in our study, as it aimed to delineate the advantage of combination of two modalities over the use of any single one for diagnosis of CSF rhinorrhea.…”
Section: Discussionmentioning
confidence: 99%